Koen van den Broek : Stuff - Davidts, Wouter (Gent : Borgerhoff & Lamberigts nv, 2019)
In his paintings, Koen Van den Broek investigates the human experience of the environment. His paintings are readily recognizable. They are descriptions of the landscape, urban architecture, constructions or details thereof. His works show traces of human presence: circus tents, highways, bridges, sewers, pipes, fragments of houses or cars, sidewalk curbs. His personal collection of photographs, snapshots that he takes on his countless journeys, are his artistic points of departure. Koen Van den Broek opts for unsightly motifs, fragments that are recurrent in any town. The artist seeks out anonymity, the general rather than the specific.
STUFF offers an overview of ten years of public art projects and contains an in-depth interview by Prof. Wouter Davidts about what this practice means for Van den Broek. For this publication, the artist made new sketches on tracing paper that provide insight into his working process and interaction with his paintings. The book is richly illustrated and contains never before published images of designs, models, work in progress and temporary, executed and non-executed artworks. (provided by publisher)
boek
Keywords: van den Broek, Koen